Ultrasensitive Molecular Sensors Based on Real‐Time Impedance Spectroscopy in Solution‐Processed 2D Materials. (3rd October 2021) - Moore, David C.; Jawaid, Ali; Busch, Robert; Brothers, Michael; Miesle, Paige; Miesle, Adam; Rao, Rahul; Lee, Jonghoon; Beagle, Lucas K.; Motala, Michael; Wallace, Shay Goff; Downing, Julia R.; et al.
Abstract: Chemical sensors based on solution‐processed 2D nanomaterials represent an extremely attractive approach toward scalable and low‐cost devices. Through the implementation of real‐time impedance spectroscopy and development of a three‐element circuit model, redox exfoliated MoS2 nanoflakes demonstrate an ultrasensitive empirical detection limit of NO2 gas at 1 ppb, with an extrapolated ultimate detection limit approaching 63 ppt. This sensor construct reveals a more than three orders of magnitude improvement from conventional direct current sensing approaches as the traditionally dominant interflake interactions are bypassed in favor of selectively extracting intraflake doping effects. This same approach allows for an all solution‐processed, flexible 2D sensor to be fabricated on a polyimide substrate using a combination of graphene contacts and drop‐casted MoS2 nanoflakes, exhibiting similar sensitivity limits. Finally, a thermal annealing strategy is used to explore the tunability of the nanoflake interactions and subsequent circuit model fit, with a demonstrated sensitivity improvement of 2× with thermal annealing at 200 °C. Abstract : The implementation of a real‐time impedance spectroscopy approach results in ultrasensitive molecular sensors based on solution processed 2D nanomaterials. Through bypassing traditionally dominant interflake interactions and selectively extracting intraflake doping effects, detection of NO2 down to 1 ppb is readily achievable with an ultimate limit of detection of 63 ppt.